Silica gel from rice hull ash: preparation and characterization - Kamath, Savita R.; Proctor, Andrew (American Association of Cereal Chemists, Inc., 2008)
Rice hulls, a waste coproduct of the rice industry, is composed of 20% silica. The objectives of this study were to develop a method to recover silica from rice hull ash and produce silica gel, and to determine the physical and chemical properties of the rice hull silica gel (RHSG) relative to Trisyl 300, a commercial silica gel. Rice hull ash consisting of 61% silica and 36% carbon was dispersed in sodium hydroxide to dissolve the silica and produce a sodium silicate solution. The latter was titrated to pH 7 with 1M sulfuric acid to obtain a gel at neutral pH. The RHSG was aged, washed, and dried under specific conditions to get a final product that was slightly basic and had a moisture content >65%. Energy dispersive X-ray spectrometry indicated that silicon was the most abundant element present in RHSG and Trisyl 300. Elemental analyses by inductively coupled plasma emission spectroscopy indicated a greater concentration of sodium and sulfur in RHSG relative to that in Trisyl 300. RHSG surface area was 258 m2/g, which was slightly more than half that of Trisyl 300 particles; the particle pore diameter was 121 Å, which was more than twice that of Trisyl 300. Fourier transform infrared spectroscopy showed similarities in chemical structures for both the silica gel samples with respect to siloxane bonds, surface silanol groups, and adsorbed water. X-ray diffraction patterns for both the samples showed a broad peak between 15 and 35°2Θ diffraction angle indicating their amorphous nature. Scanning electron micrographs revealed that RHSG particles ranged in sizes from <5 to >40 μm, whereas Trisyl 300 particles were smaller, ranging in sizes from <5 to 25 μm and had a more uniform appearance. Silica gel production from rice hull ash alleviates the rice hull waste disposal problem and creates a commercially viable value-added product. RHSG has wide-ranging applications in a variety of industries, such as vegetable oil refining, pharmaceuticals, cosmetics, and paints.